Maternal dairy fat diet does not influence neurotrophin levels and cognitive performance in the rat offspring at adult age. Issue 71 (December 2018) - Jawale, Shruti; Joshi, Sadhana; Kale, Anvita
Highlights: Maternal dairy fat consumption lowered BDNF in the pup brain at birth. Maternal dairy fat consumption did not affect the BDNF and NGF in the adult offspring. Maternal dairy fat consumption did not affect the cognition in adult rat offspring. Abstract: Cognitive development may be influenced by maternal nutrition especially fats. Indian population is vegetarian and main source of fat is dairy. This study investigates the effect of dairy fat consumption during pregnancy in an animal model on fatty acids, brain neurotrophins (brain derived neurotrophic factor: BDNF; and nerve growth factor: NGF) and cognitive performance in adult offspring. Pregnant Wistar rats were assigned to control (Control C) and four treatment groups: High fat diet (HFD); High fat diet supplemented with omega-3 fatty acids (HFDO); High fat diet deficient in vitamin B12 ( HFBD); High fat deficient in vitamin B12 supplemented with omega-3 fatty acids (HFBDO). Half the dams were dissected on d20 of gestation, and the brains of their pups were collected. The remaining dams delivered on d22 of gestation and were assigned to a control diet. The cognitive performance of these adult offspring was assessed at 6 mo of age. Brain fatty acids were comparable to control in the pups at birth and offspring at 6 mo of age. The protein levels of BDNF in the pup brain at birth were lower in both the HFD (p < 0.01) and HFBD (p < 0.05) groups as compared to control. The mRNA levels of TrK B were lower (p < 0.05) in the pup brain at birth in the HFD as compared to control group. In the offspring at 6 mo of age the protein levels of BDNF and NGF in all the treatment groups were similar to that of control. However, the mRNA levels of only BDNF (p < 0.01 for both) were higher in the HFBD group as compared to both control and HFD groups. The cognitive performance of the adult offspring from various dietary groups was similar to control. In conclusion, consumption of a maternal high dairy fat diet although lowered the levels of brain BDNF in the pup at birth it does not affect the cognitive health of the adult offspring.